2018
DOI: 10.1088/1748-3190/aabf4c
|View full text |Cite
|
Sign up to set email alerts
|

Flow interactions of two- and three-dimensional networked bio-inspired control elements in an in-line arrangement

Abstract: We present experiments that examine the modes of interaction, the collective performance and the role of three-dimensionality in two pitching propulsors in an in-line arrangement. Both two-dimensional foils and three-dimensional rectangular wings of AR  =  2 are examined. In contrast to previous work, two interaction modes distinguished as the coherent and branched wake modes are not observed to be directly linked to the propulsive efficiency, although they are linked to peak thrust performance and minimum pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 39 publications
3
43
0
Order By: Relevance
“…In order to simplify the problem and consider the fact that most fish and birds are using flapping fins/wings to generate propulsive forces, fish schools and bird flocks are often simplified as two flapping foils in regular arrangements (Dewey et al 2014). It has been indicated that the hydrodynamic benefit can be achieved by flapping foils in a variety of regular arrangements, including the tandem arrangement (Kurt & Moored 2018), the side-by-side arrangement (Dewey et al 2014) and the staggered arrangement (Huera-Huarte 2018). In the tandem formation, the performance augmentation can be achieved by the upstream body when the separation distance is small .…”
Section: Introductionmentioning
confidence: 99%
“…In order to simplify the problem and consider the fact that most fish and birds are using flapping fins/wings to generate propulsive forces, fish schools and bird flocks are often simplified as two flapping foils in regular arrangements (Dewey et al 2014). It has been indicated that the hydrodynamic benefit can be achieved by flapping foils in a variety of regular arrangements, including the tandem arrangement (Kurt & Moored 2018), the side-by-side arrangement (Dewey et al 2014) and the staggered arrangement (Huera-Huarte 2018). In the tandem formation, the performance augmentation can be achieved by the upstream body when the separation distance is small .…”
Section: Introductionmentioning
confidence: 99%
“…Garrick's solution assumes potential flow over: (a) a two-dimensional, (b) infinitesimally-thin hydrofoil, (c) undergoing small amplitude, (d) harmonic motions with (e) a non-deforming, planar wake behind the hydrofoil. Moreover, since this is an inviscid flow solution, induced shedding of vorticity at the leading edge from interaction with the gust field is not accounted for, even though it is known to exist in schooling interactions [12,19]. In the present study, we will compare direct force measurements of the follower hydrofoil to the quasi-steady Garrick solution with three-dimensional corrections.…”
Section: Linear Unsteady Hydrofoil Theorymentioning
confidence: 99%
“…These highly three-dimensional spatial configurations found within collectives can be decomposed into canonical in-line, side-by-side, or tip-to-tip arrangements as presented in Figure 1 . To date, these interactions have mostly been studied for propulsors in in-line arrangements [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], although a few efforts have been made to understand interactions in side-by-side arrangements [ 20 , 21 , 22 , 23 ], as well as staggered arrangements [ 24 , 25 , 26 , 27 ]. Here, our focus is on the propulsive performance and flow interactions in in-line , and staggered arrangements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of works have investigated multiple flapping foils interacting in a fluid (Sparenberg & Wiersma 1975; Akhtar et al. 2007; Wang & Russell 2007; Boschitsch, Dewey & Smits 2014; Kurt & Moored 2018; Lin et al. 2019).…”
Section: Introductionmentioning
confidence: 99%